A45. Icu Management and Outcomes: Prediction, Procedures and Pot Pourri 2010
DOI: 10.1164/ajrccm-conference.2010.181.1_meetingabstracts.a1646
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Obesity And Outcomes In Critically Ill Patients

Abstract: O besity, defi ned as a BMI between 30 and 39.9 kg/m 2 , and extreme or severe obesity, defi ned as a BMI Ն 40 kg/m 2 , are increasingly prevalent in the United States. 1 During the same time period, 4.2% of men and 7.2% of women were extremely obese. Overweight, obesity, and extreme obesity are associated with increased all-cause mortality among the general population, in both genders. 1 However, in critically ill patients, recent evidence suggests that obese and extremely obese patients do not have increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 18 publications
(25 reference statements)
2
47
0
Order By: Relevance
“…In our population, we found higher prevalence of obesity and morbid obesity and lower prevalence of underweight patients when compared with other reports [11,21,28 and 29]. In agreement with the findings of Martino et al, [29], we found an association between BMI categories and the increased requirement for MV and prolonged ICU stay. Our finding that overweight/obese and severely obese patients were more often to be female when compared with underweight and normal weight patients has been rarely reported for ICU populations [28].…”
Section: Discussionsupporting
confidence: 92%
“…In our population, we found higher prevalence of obesity and morbid obesity and lower prevalence of underweight patients when compared with other reports [11,21,28 and 29]. In agreement with the findings of Martino et al, [29], we found an association between BMI categories and the increased requirement for MV and prolonged ICU stay. Our finding that overweight/obese and severely obese patients were more often to be female when compared with underweight and normal weight patients has been rarely reported for ICU populations [28].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, obesity has been identified as a risk factor for death from influenza A-associated ARDS, 6,7 although these studies were small. Larger adult critical care studies have shown that although obesity may be associated with longer ICU stay, when controlling for severity of illness, the mortality is the same 8,9 or lower 10 than for nonobese adults. In non-ICU settings, a 2013 metaanalysis 11 of 2.88 million adult patients found that the overweight group had a statistically significant lower all-cause mortality.…”
mentioning
confidence: 99%
“…25 Chronic obesity results in pathophysiological alterations in all major organ systems; the main derangements are in cardiovascular, respiratory, and metabolic functions. 26 Many recent studies [27][28][29][30][31][32][33][34][35][36] on morbidity and mortality rates of obese critically ill patients have indicated that although obesity may not have an effect on hospital mortality rates (and may even have a protective effect), obese patients tend to have increased hospital morbidity as evidenced by longer duration of mechanical ventilation, longer ICU length of stay, longer hospital length of stay, and increased rate of infection. Missed or delayed detection of malnutrition in these patients may contribute to these adverse outcomes.…”
Section: Risk For Malnutrition In Obese Critically Ill Patientsmentioning
confidence: 99%